Merdeka Curriculum: Implementation Of Pancasila Student Profile Enhancement Project (P5) In State High School 1 Kedamean - Rizkina, Muthiara Nurlaila; Mudrikah, Ikah; Nisa, Nabillah Zuhrotun; Dina, Tsabitah Farah; Suliyanah, Suliyanah; Deta, Utama Alan; Suprapto, Nadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Merdeka's curriculum has been developed as a more flexible curriculum framework while focusing on essential subjects and developing the character and competence of students. In addition, students are also given the opportunity to develop the necessary skills in social, cultural, and economic environments. To realize these aspirations, the Merdeka curriculum was born with an innovation in the form of the Pancasila Student Profile Enhancement Project (P5). The purpose of this study is to find and gather data on the implementation of the independent curriculum in State High School 1 Kedamean for the P5 project. To provide useful and easy-to-understand information for the reader, the study uses a qualitative descriptive approach to describe the subject, the situation, and the data obtained during observations and questions. The results of this research show that the curriculum in State High School 1 Kedamean has been implemented well and is running well, but there are still many shortcomings and difficulties in its implementation. As a leader, the head of school must have the ability to change the perspective of human resources in their educational environment so that the independent curriculum can be applied to the maximum. Overall it can be said that P5 has run 90% with obstacles faced by schools such as teacher conformity with policy, where teachers are still in the process of adapting themselves to the characteristics of the Merdeka curriculum. The results of these findings can be used as a study for developing the implementation of the P5 program in other schools.